FACTORS INFLUENCE TO PURCHASE BRANDED EDIBLE OIL AMONG RURAL WOMEN IN TUTICORIN DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the study is to know the factors influence the rural women to purchase branded edible oil and the product factors influencing perception towards edible oil in Tuticorin district.Descriptive research method has been used in this study. The survey research method used. Rural women were asked a variety of questions.This study is based on both primary and secondary data. Secondary data was collected from research articles, journals, magazines, government surveys and reports (Both Central and State), Planning Commission reports etc. Primary data was collected through well structured interview schedule from rural women who are used edible oil in Tuticorin district.For the present study, the respondents were chosen to participate in the study based on the judgment of the researcher as to whom the researcher found fit to answer the questions and based on the accessibility of the respondent to the researcher. 200 sample respondents were selected for the study by using judgement sampling method. It is found that the main product factors influencing perceptiontowards edible oil among rural women who are in the age group of below 30 years are suitability of all ages and price. It is observed that the main product factors influencing perceptiontowards edible oil among rural women who are in the age group of 31 to 40 years are health benefits and suitability of all ages.